The Relationship Between Completeness of Basic Immunization and Maternal Visits to Posyandu and the Nutritional Status of Toddlers - Adinda Zahranisa; Diyan Indrayani; Saur Sariaty; Yulidar Yanti (Jurnal Kebidanan, 2025)
The problem of toddler nutrition in Indonesia is still high. Bandung Regency ranks third highest in terms of toddler nutrition problems. Poor nutritional status in toddlers can hinder physical growth and cognitive development, and make them more susceptible to disease. In addition, the completeness of immunizations and visits by mothers to health posts remain low. Low coverage of basic immunizations and regular visits to health posts are contributing factors to this issue. The purpose of this study is to determine the relationship between the completeness of basic immunizations and maternal visits to health posts with infantnutrition status. The study design is quantitative with a case-control design. The study population is all infants aged 12–59 months in Hegarmanah Village, with a sample size of 66 infants divided into case (malnourished) and control (well-nourished) groups. The sampling technique used simple random sampling. Data collection utilized observation forms, KIA books, and anthropometric measurement tools. Results analysis using the chi-square test showed between the completeness of basic immunization and the nutritional status of infants with a p-value< α (0.05), as well as between mothers' visits to the health post and the nutritional status of infants with a p-value < α (0.05). Infants who did not receive complete basic immunization were 3.75 times more likely to experience malnutrition, and infants whose mothers did not actively visit the posyandu were 3 times more likely to experience malnutrition. Strategic steps are needed to increase community interest and motivationfor regular posyandu visits and to complete immunization.